Improved InGaN/GaN light-emitting diodes with a p-GaN/n-GaN/p-GaN/n-GaN/p-GaN current-spreading layer - Sun, Xiaowei (2013)
This work reports both experimental and theoretical studies on the InGaN/GaN light-emitting diodes (LEDs) with optical output power and external quantum efficiency (EQE) levels substantially enhanced by incorporating p-GaN/n-GaN/p-GaN/n-GaN/p-GaN (PNPNP-GaN) current spreading layers in p-GaN. Each thin n-GaN layer sandwiched in the PNPNP-GaN structure is completely depleted due to the built-in electric field in the PNPNP-GaN junctions, and the ionized donors in these n-GaN layers serve as the hole spreaders. As a result, the electrical performance of the proposed device is improved and the optical output power and EQE are enhanced.